2017
DOI: 10.12890/2017_000662
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Biopsy in Henoch-Schönlein Purpura: A Great Diagnostic Contribution

Abstract: Henoch-Schönlein purpura is an IgA-mediated immune vasculitis which is characterized by purpuric lesions and osteoarticular, intestinal and sometimes renal manifestations. The histopathological substrate of this entity is leucocytoclastic vasculitis (LCV) with IgA deposits seen on immunohistochemistry. We here report the case of a 27-year-old woman with abdominal pain and cutaneous purpura. Upper and lower endoscopic exploration showed purpuric lesions in the rectum but not in the stomach. Skin biopsy revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Akkari et al have reported IgA deposition despite the absence of lesion at endoscopy previously. [11] One patient who visited hospital for abdominal pain and loose stool underwent EGD and early gastric cancer was incidentally found and histologically confirmed as well-differentiated adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Akkari et al have reported IgA deposition despite the absence of lesion at endoscopy previously. [11] One patient who visited hospital for abdominal pain and loose stool underwent EGD and early gastric cancer was incidentally found and histologically confirmed as well-differentiated adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic criteria include palpable purpura, age onset ≤20 years, acute abdominal pain, and compatible biopsy of an affected organ, with the presence of two or more giving a sensitivity and specificity approximately 90% in separating adult patients with HSP from those with other causes of vasculitis 5 . Biopsy and direct immunofluorescence may contribute and confirm the diagnosis, especially in adult‐patient population, where the clinical suspicion for HSP is low 6 …”
Section: Figurementioning
confidence: 99%
“…5 Biopsy and direct immunofluorescence may contribute and confirm the diagnosis, especially in adultpatient population, where the clinical suspicion for HSP is low. 6 Ciprofloxacin induced vasculitis is a rare adverse event, being reported in the literature only few times, usually as leukocytoclastic F I G U R E 1 Macroscopic findings of purpura on lower extremities vasculitis (LCV) or mononuclear-cell infiltrate. 7 HSP related to ciprofloxacin, is an unpredictable, idiosyncratic drug reaction, probably mediated by immunologic mechanisms, arising from patients' genetic differences, and probably having a strong HLA dependence.…”
mentioning
confidence: 99%
See 1 more Smart Citation